2020
DOI: 10.1038/s41598-020-77965-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiments to understand crystallization of levitated high temperature silicate melt droplets under low vacuum conditions

Abstract: We report experiments on crystallization of highly undercooled forsterite melt droplets under atmospheric and sub-atmospheric pressure conditions. Experiments have been conducted under non-contact conditions using the principles of aero-dynamic levitation. Real time dynamics of solidification, along with the transient evolution of surface textures, have been recorded using high speed camera for three cooling rates. These images have been matched with the time-tagged temperature data to understand the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…Recent crystallization experiments on Earth using laser heating of Mg 2 SiO 4 spherules which were levitated on a gas jet led to the formation of a dendritic microstructure, which is clearly different from the fabric observed here (Mishra et al. 2020). Consequently, the observed microstructure seems to be the result of crystallization in microgravity without any contact to sample chamber walls, which would imply that this feature probably cannot be observed in experiments on Earth.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Recent crystallization experiments on Earth using laser heating of Mg 2 SiO 4 spherules which were levitated on a gas jet led to the formation of a dendritic microstructure, which is clearly different from the fabric observed here (Mishra et al. 2020). Consequently, the observed microstructure seems to be the result of crystallization in microgravity without any contact to sample chamber walls, which would imply that this feature probably cannot be observed in experiments on Earth.…”
Section: Discussioncontrasting
confidence: 86%
“…2015; Mishra et al. 2020). Recent crystallization experiments on Earth using laser heating of Mg 2 SiO 4 spherules which were levitated on a gas jet led to the formation of a dendritic microstructure, which is clearly different from the fabric observed here (Mishra et al.…”
Section: Discussionmentioning
confidence: 99%
“…The wire method is unsuitable for accurately reproducing the crystallization process in the protoplanetary disk because the contact points between the starting materials and wires work as heterogeneous nucleation sites and facilitate crystallization. For this reason, levitation experiments have been conducted to simulate chondrule formation (Tsukamoto et al 1999;Nagashima et al 2006Nagashima et al , 2008Pack et al 2010;Mishra et al 2020;Shete et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Chondrule formation took place under reducing conditions (e.g., Ebel & Grossman 2000;Grossman et al 2008;Tenner et al 2015;Villeneuve et al 2015), and some of the following levitation experiments simulated those conditions. Mishra et al (2020) conducted levitation experiments in a chamber filled with Ar gas under subatmospheric pressure and revealed that the latent heat of crystallization was removed more rapidly than under atmospheric conditions, resulting in faster cooling of the experimental samples that simulated chondrules. Consequently, this leads to smaller forsterite crystal sizes than under atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%